2019
DOI: 10.1111/jog.14158
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopic scoring indexes in the evaluation of cervical lesions with the cytological result of atypical squamous cells, cannot exclude high‐grade lesion

Abstract: Aim: Colposcopic indexes including Reid index and Swede score were developed to make the colposcopy more objective. The aim of our study was to evaluate the significance of colposcopic indexes in the evaluation of ASC-H cervical lesions. Methods: We carried out a cross-sectional study in the Clinic of Obstetrics and Gynecology between January 2013 and December 2018. The study included 535 women, from which 66 women had a cytological result ASC-H. Scoring of all colposcopic findings was assessed according to Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Under colposcopy, white acetic acid epithelium, with the severity of the lesion positively associated with the whiteness of the epithelium, white glands and rings, heterogenous vessels and punctured vessels were observed. The Reid colposcopy index (RCI) score was proposed by Reid in 1984; it can reduce the subjectivity of colposcopy diagnosis and is currently the most widely accepted colposcopy scoring system ( 26 ). Previous studies ( 27 , 28 ) reported that colposcopy diagnosis using RCI has a good consistency with histopathological diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Under colposcopy, white acetic acid epithelium, with the severity of the lesion positively associated with the whiteness of the epithelium, white glands and rings, heterogenous vessels and punctured vessels were observed. The Reid colposcopy index (RCI) score was proposed by Reid in 1984; it can reduce the subjectivity of colposcopy diagnosis and is currently the most widely accepted colposcopy scoring system ( 26 ). Previous studies ( 27 , 28 ) reported that colposcopy diagnosis using RCI has a good consistency with histopathological diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…account for 30% [ 4 7 ]. Currently, colposcopy-guided biopsy with histopathology is considered the gold-standard method for the diagnosis of cervical cancer and cervical intraepithelial neoplasia [ 8 , 9 ]. By applying acetic acid (3–5%) and Lugol’s iodine, a colposcopist can detect abnormalities in cervical visual appearance based on changes in the epithelium and blood vessels [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…account for 30% (4)(5)(6)(7). Currently, colposcopy-guided biopsy with histopathology is considered the gold-standard method for the diagnosis of cervical cancer and cervical intraepithelial neoplasia (8,9). By applying acetic acid (3-5%) and Lugol's iodine, a colposcopist can detect abnormalities in cervical visual appearance based on changes in the epithelium and blood vessels (10).…”
Section: Introductionmentioning
confidence: 99%